A report on the practice in industry training in fish capture. - Mariano, Conrado C. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1957)
Many students are interested in the study of Ichythyology. Some are interested in the study of gear construction and others. The study of fresh water and marine fisheries is of general interest. I am one of the students who have taken the course in fish capture and its general ramifications. After completing the subject as prescribed by the school of fisheries I am to undergo six months of field training as a necessary pre-requisite for graduation. The writer is now required to submit report on factual dissertation of his daily work and accomplishments.
Keywords: Fish-Capture.